Environmental epidemiological risk of arsenic in the Moquegua region, Peru - Rodríguez-Salas, Manuel Aníbal (2025)
The study analyzed the environmental epidemiological risk of arsenic in the Moquegua region, Peru, between January and August 2025. A descriptive study design was applied, and a total of 50 environmental samples were collected, including water, soil, bovine milk, and cattle hair, from the watersheds of the Coralaque River (General Sánchez Cerro province) and the Tambo River (Mariscal Nieto province). Arsenic concentrations were determined by hydride generation atomic absorption spectrometry (HGAAS). The results showed mean concentrations of 0.123 ± 0.015 mg/L in the Coralaque River and 0.095 ± 0.012 mg/L in the Tambo River, exceeding the regulatory limit (0.010 mg/L) by 9.5 to 12.3 times. In agricultural soil from the Torata Valley, arsenic levels of 22.8 ± 3.7 mg/kg were detected, while bovine milk and cattle hair presented 0.0916 ± 0.046 mg/kg and 0.9616 ± 0.53 mg/kg, respectively. These values confirmed the bioaccumulation of the metalloid and its trophic transfer. It was concluded that arsenic contamination in Moquegua constitutes a structural environmental epidemiological risk, highlighting the need to adjust Peruvian regulations and strengthen intersectoral health surveillance.